Analisis Keseimbangan Ekonomi Tiga Sektor Dalam Perspektif Makro Ekonomi - Hafidatul Husna; Armina Khoiriyah Nasution; Indah Afriliani; Nur Fitriana (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study analyzes the economic balance in the three main sectors, namely companies, government, and households in a macroeconomic perspective. This research uses an analytical descriptive approach with a focus on the interaction and relationship between the three sectors. Firms act as producers of goods and services, as well as job creators that affect the level of production and national income. The government functions as a regulator and manager of fiscal policy that includes state spending and revenue, as well as intervention in the economy to maintain economic stability. Households, as the main consumers, influence aggregate demand and the level of savings, which is the source of investment. Economic equilibrium is achieved when there is effective coordination between production, consumption, and government policies, which is reflected in economic indicators such as Gross Domestic Product (GDP), inflation, and unemployment rate. The study found that imbalances in any one sector can lead to broader macroeconomic imbalances. Factors such as monetary policy, demographic changes, and globalization also play an important role in the dynamics of economic balance. This analysis provides a deeper understanding of the importance of synergy between firms, government, and households in achieving sustainable economic stability.